Spatially Arrayed Long Period Gratings in Multicore Fiber by Programmable Electrical Arc Discharge - Ruoxu Wang; Ming Tang; Songnian Fu; Zhenhua Feng; Weijun Tong; Deming Liu (IEEE Photonics Journal)
Based on electrical arc discharges mechanisms, we inscribed spatially arrayed long period gratings (LPGs) into a heterogeneous seven-core fiber. The LPG fabrication platform was built upon the commercial fiber fusion splicer with a self-developed real-time control software. With the help of homemade fan-in/fan-out multiplexer, the high-quality grating spectra in seven cores are measured. The largest resonant dip of −42 dB and minimum insertion loss of 0.5 dB are achieved in the central core. To demonstrate potentials of the spatially diversified gratings, we measured the strain and temperature simultaneously with the spatial response matrix to eliminate the cross sensitivity. Accurate sensing results have been achieved with relative errors less than 4%.